Primary frequency regulation in power networks with ancillary service from load-side participation - Kasis, Andreas; Devane, Eoin; Lestas, Ioannis (Apollo - University of Cambridge Repository, 2019)
We consider the problem of designing distributed generation and demand control schemes that provide ancillary service in primary frequency regulation in power networks such that stability and fairness in the power allocation can be guaranteed. It is desirable in such schemes that load side participation in frequency control is activated only when the frequency exceeds prescribed thresholds so as to avoid frequent intervention in the operation of loads. This, however, leads to nonlinear control schemes with vector fields with discontinuous derivatives. In this paper, we investigate how stability and optimality may be ensured when such dynamics are considered. We show that subgradient methods can be used to derive decentralised conditions that ensure optimality of the equilibrium points. Decentralised conditions for asymptotic stability that are valid in this context are also provided. We illustrate our results with simulations on the IEEE 68 bus system, where it is demonstrated that the inclusion of controllable loads offers improved transient behaviour and that an optimal power allocation among controllable loads is achieved.